Improving Learning Achievement of Theme 6 Temperature and Heat Sub-Matter through the Application of Simulation Learning Methods in Elementary School - Indarti Kustiyantini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The research used is two-cycle classroom action research (PTK). The aim of this research is to improve student learning achievement by using a simulation learning model. The subjects of this research are class V students in the second semester of the 2021/20222 academic year at SD Negeri 2 Gedaren, Jatinom District. Klaten Regency, totaling 23 students, by carrying out improvements from the pre-cycle through Cycle 1 and Cycle 2. The application of the Simulation Learning Method has been proven to be able to improve learning achievement for theme 6 sub-material Temperature and Heat for class V students in the second semester of the 2021/2022 academic year. Application of the Simulation Learning Method to subject Theme 6 Sub-Material Temperature and Heat. The 6th grade students of SDN 2 Gedaren obtained the following results: The average pre-cycle gain was 61% with student completion at 47%, this was because they had not used the Simulation Learning Method. The average score for cycle I is around 73% with students completing 72%, this is because they have used the Simulation Learning Method. The average score for cycle II is 87.8 with completeness reaching 100%. This is because they have been given material using the method. Simulation Learning. Based on the consistently increasing grades, it is concluded that the application of the Simulation Learning Method can improve student learning achievementn